Proyecto para la implementación de un complejo ecoturístico en el sector de el colorado “cascadas de manuel” (ruta guabo-Guayaquil) - Almeida Aguilar, Mayra Mercedes (2009)
The objective of this research is to determine the feasibility of creating an ecotourism complex, you choose your area of El Colorado which is near the canton Guabo because nature has provided us with eight beautiful waterfalls called "Cascadas De Manuel" they possess unparalleled properties in addition to weather an extraordinary ecological diversity represented in its flora and fauna. There is a short journey that is not in good condition, reason why many tourists and natives of the province of El Oro do not visit these waterfalls. Besides that there are no adequate infrastructure to exploit the tourist authority provided by this sector, which consequently brings a lack of natural wealth in Ecuador. Also in this sector is lacking an establishment that provides food service for visitors.